Onvansertib and paclitaxel combined in platinum-resistant ovarian carcinomas. (May 2022) - Affatato, Roberta; Chiappa, Michela; Guffanti, Federica; Ricci, Francesca; Formenti, Laura; Fruscio, Robert; Jaconi, Marta; Ridinger, Maya; Erlander, Mark; Damia, Giovanna
Background: Ovarian carcinoma is extremely sensitive to (platinum-based) chemotherapy; however, most patients will relapse with platinum-resistant disease, badly affecting their prognosis. Effective therapies for relapsing resistant tumors are urgently needed. Methods: We used patient-derived xenografts (PDXs) of ovarian carcinoma resistant to cisplatin (DDP) to test in vivo the combination of paclitaxel (15 mg/kg i.v. once a week for 3 weeks) and onvansertib, a plk1 inhibitor, (50 mg/kg orally 4 days a week for 3 weeks). The PDX models were subcutaneously (s.c.) or orthotopically transplanted in nude mice and antitumor efficacy was evaluated as tumor growth inhibition and survival advantages of the combination over untreated and single agent treatment. Results: The combination of onvansertib and paclitaxel was very well tolerated with weight loss no greater than 15% in the combination group compared with the control group. In the orthotopically transplanted PDXs, single onvansertib and paclitaxel treatments prolonged survival; however, the combined treatment was much more active, with median survival from three- to six-fold times that of untreated mice. Findings were similar with the s.c. transplanted PDX, though there was greater heterogeneity in tumor response. Ex vivo tumors treated with the combination showed greater induction of γH2AX, marker of apoptosis and DNA damage, and pSer10H3, a marker of mitotic block. Conclusion: The efficacy of onvansertib and paclitaxel combination in these preclinical ovarian cancer models supports the clinical translatability of this combination as an effective therapeutic approach for platinum-resistant high-grade ovarian carcinoma.